IMPLEMENTATION OF INCLUSIVE EDUCATION POLICY IN THE FREEDOM TO LEARN - Wahyudi Widodo (Jurnal Scientia, 2023)
Inclusive education is something that is relatively new in the realm of Indonesian education. This special education is intended for students who require special attention when participating in learning activities due to physical, emotional, mental, social disorders or students who have special intelligence and talent potential. Inclusive education is the implementation of an education system that provides opportunities for students and does not differentiate between children with normal conditions and special needs so that the learning process can be followed in the same educational environment evenly. Inclusive schools are schools that provide inclusive education. This means a school that accepts all students from different backgrounds and abilities in the same class. Inclusive schools also implement an independent learning curriculum. Independent learning is learning that was initially based on educators to become a learning system that is centered on students. independent learning provides free space for children with special needs to be able to explore themselves and the environment. One of the goals of implementing this education is to achieve an even distribution of quality learning systems that are appropriate based on the circumstances, skills and needs of each student and can be realized well. This research uses a qualitative descriptive approach with a library research type. The data collection technique used is literature study. The results of writing this paper aim to find out about (1) inclusive education policies, (2) freedom to learn, (3) the concept of inclusive education